2007
DOI: 10.1002/tea.20191
|View full text |Cite
|
Sign up to set email alerts
|

The influence of core teaching conceptions on teachers' use of inquiry teaching practices

Abstract: This article investigates three teachers' conceptions and use of inquiry-based instructional strategies throughout a professional development program. The professional development program consisted of a 2-week summer inquiry institute and research experience in university scientists' laboratories, as well as three academic year workshops. Insights gained from an in-depth study of these three secondary teachers resulted in a model of teacher conceptions that can be used to direct future inquiry professional dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 56 publications
(43 reference statements)
8
148
0
10
Order By: Relevance
“…Within this set of orientations one usually finds that a more direct orientation is more teacher-directed, while an inquiry orientation is a more learner-directed approach (NRC, 2000b, p. 29). A more direct orientation aligns more with information transmission than independent thinking (Lotter et al, 2007). Our orientation spectrum also encompasses many of the orientation types proposed by Magnusson, Krajcik, and Borko (1999), including process, didactic, activity-driven, discovery, inquiry, and guided inquiry, in a form aligned closely with our project goals.…”
Section: Science Teaching Approachesmentioning
confidence: 77%
See 1 more Smart Citation
“…Within this set of orientations one usually finds that a more direct orientation is more teacher-directed, while an inquiry orientation is a more learner-directed approach (NRC, 2000b, p. 29). A more direct orientation aligns more with information transmission than independent thinking (Lotter et al, 2007). Our orientation spectrum also encompasses many of the orientation types proposed by Magnusson, Krajcik, and Borko (1999), including process, didactic, activity-driven, discovery, inquiry, and guided inquiry, in a form aligned closely with our project goals.…”
Section: Science Teaching Approachesmentioning
confidence: 77%
“…In the science education literature, teaching orientation can refer to a number of different ideas. The orientation dimension we focus upon in our work is somewhat less complex than the full 'sets of beliefs that teachers hold' (Friedrichsen, Van Driel, & Abell, 2011, p. 372), and at the same time reflects aspects of both the National Research Council descriptions and the dimensions of influential teacher conceptions that Lotter, Harwood, and Bonner (2007) describe. It provides a spectrum of common orientations along a direct-inquiry continuum, described in greater detail in the next section.…”
Section: Science Teaching Approachesmentioning
confidence: 99%
“…In her recent work, Crawford (2007) argues that teachers' "complex set of personal beliefs about teaching and of science" influence teaching science as inquiry (p. 613), echoing the efforts of Woodbury and Gess-Newsome (2002). The work of Harwood, Hansen, and Lotter (2005) and Lotter et al (2007) support the notion that teachers' beliefs influence how they teach as well as how they respond to professional development. Anderson (2002) explains, It is common to talk about barriers or obstacles that must be overcome for teachers to acquire an inquiry approach to teaching.…”
Section: Theoretical Framework Teacher Knowledge and Beliefsmentioning
confidence: 99%
“…In her work with 10 secondary science teachers, Blanchard (2006) found teachers' conceptions of inquiry to be defined in applied, practical ways embedded in their classroom practices and described in terms of what the teacher was doing or what the student was doing. Recent work by Lotter, Harwood, and Bonner (2007) suggests that teachers' core teaching conceptions (views of science, the purpose of education, students, and effective teaching practices) influence their receptivity to inquiry-based teaching. In their study, Lotter et al found that viewing science as a set of facts to be amassed worked against teachers' acceptance of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore these conceptions are crucial in how the teachers conceptualize what represents the best way to teach their subject. This line of research has been very active and there is a wide range of studies exploring how these teaching conceptions affect students' learning and their use of learning strategies (Lotter;Harwood & Bonner, 2007;Muis & Franco, 2009;Van Petegem & Donche, 2006). According to Monereo y Badia (2011) these three categories of conceptions are the ones that build up the teacher identity influencing one another.…”
Section: Teacher Identity: Definitionmentioning
confidence: 99%